META ANALISIS TUTORIAL ONLINE UNIVERSITAS TERBUKA - Sri Suharmini Wahyuningsih; Tri Darmayanti; Arifah Bintarti (LPPM Universitas Terbuka, 2019)
Online tutorial service was a learning support services provided by the Universitas Terbuka (UT) for its students. In the distance education system, the learning process could be done through the internet. Research on online tutorial learning and services has been done by UT lecturers. This article aimed to map research related to UT's online tutorials, both in the form of research reports and those that have been published in journals. The purpose of mapping was to find out what research topics regarding online tutorials that have been conducted. The research method used was the meta-analysis method, combining various analyzes which then produced a global analysis of online tutorials. The results of this study were online tutorial research could be categorized into five topics, namely a) the relationship between online tutorial values ​​and final exam scores; b) organizing online tutorials; c) the quality of online tutorials; d) online tutorial accessibility; and e) online tutorials as a research tool. Students rated the implementation of online tutorials as good and they were satisfied. The value of online tutorials could contribute to the value of final exam scores. However, the accessibility of online tutorials was still low because it depended on the network and students’ discipline and activeness. Layanan tutorial online merupakan layanan bantuan belajar yang diberikan Universitas Terbuka (UT) untuk para mahasiswanya. Dalam sistem pendidikan jarak jauh proses pembelajaran dapat dilakukan melalui jaringan internet. Penelitian tentang layanan dan pembelajaran tutorial online sudah banyak dilakukan oleh dosen UT. Artikel ini bertujuan untuk memetakan penelitian yang berhubungan dengan tutorial online UT, baik dalam bentuk laporan penelitian maupun yang sudah dipublikasikan di jurnal. Tujuan pemetaan adalah untuk mengetahui apa saja topik penelitian mengenai tutorial online yang sudah dilakukan. Metode penelitian yang digunakan adalah metode meta analisis, menggabungkan berbagai analisis yang kemudian menghasilkan analisis global mengenai tutorial online. Hasil dari penelitian ini adalah penelitian tutorial online dapat dikategorikan menjadi lima topik, yaitu: a) Hubungan nilai tutorial online dengan nilai UAS; b) Penyelenggaraan tutorial online; c) Kualitas tutorial online; d) Aksesibilitas tutorial online; dan e) Tutorial online sebagai sarana atau alat penelitian. Mahasiswa menilai penyelenggaraan tutorial online sudah baik dan mahasiswa merasa puas. Nilai tutorial online dapat berkontribusi terhadap nilai UAS. Namun aksesibilitas tutorial online masih rendah karena bergantung kepada jaringan serta kedisiplinan dan keaktifan mahasiswa.